Business Process Reengineering of the Book Lending and Returning System for Library Using BPMN - Ulil Fikri Warvana; Wildan Suharso (bit-Tech, 2025)
School libraries support the learning process by providing information sources that enrich students' insights. Bangselok 1 State Elementary School (SDN) library faces problems in its management system, which is still conventional, making it less efficient in data collection, borrowing, and returning books. This research aims to improve the efficiency of the school library book lending process by using Process Reengineering (BPR) and Business Process Modelling Notation (BPMN). The current process of borrowing books was inefficient, taking 16-22 minutes for borrowing and 12-18 minutes for returning books, with throughput efficiency ranging from 40% to 100%. The conventional method was identified as time-consuming and error-prone, leading to wastage of resources. A redesigned process was proposed, eliminating unnecessary steps and automating tasks, which reduced the total time, achieving a throughput efficiency of 100% in both scenarios. In addition, integrating an Android-based library management system is recommended to facilitate new processes, improve data accuracy, and enhance service quality. Implementing this system is expected to optimize library operations and support the school's educational goals by providing timely access to resources. This study shows that implementing BPR and BPMN can significantly improve library processes, benefitting educators and students at SDN Bangselok 1 and emphasizing the need to modernize library management practices.